Does invasive acupuncture improve postoperative ileus after colorectal cancer surgery? A systematic review and meta-analysis - Zhao, Xiaohu; Si, Shangkun; Liu, Xin; Liu, Jingxuan; Zhang, Dongbin; Mu, Yuejun; Hou, Aihua (Frontiers in Medicine, 2023)
Background: Postoperative ileus (POI) is one of the main complications after colorectal cancer (CRC) surgery, and there is still a lack of effective treatment. At present, the evidence for improvement of POI by invasive acupuncture (manual acupuncture and electroacupuncture, IA) is limited. This meta-analysis of randomized controlled trials (RCTs) aims to systematically review and evaluate the effect of IA in improving POI after CRC surgery. Methods: This meta-analysis was reported according to PRISMA statement and AMSTAR guidelines. The retrieval time was from the inception to February 2023. The RCTs were screened By searching the databases (PubMed, Ovid, Embase, Cochrane Library, China National Knowledge Infrastructure, VIP Database, Sinomed Database, and WANFANG). Two independent investigators screened and extracted the data, assessed the risk of bias and performed statistical analysis. The statistical analysis was carried out by RevMan5.3. The PROSPERO International Prospective Register of Systematic Reviews received this research for registration(CRD42023387700). Results: 13 studies with 795 patients were included. In the primary outcome indicators: the IA group had shorter time to the first flauts (stand mean difference [SMD], -0.57; 95% confidence interval [CI], -0.73 to -0.41, P < 0.00001), shorter time to the first defecation (mean difference [MD], -4.92 hours, 95% CI -8.10 to -1.74 hours, P = 0.002) than the blank/sham stimulation(B/S) group. In the secondary outcome indicators: the IA group had shorter time to the first bowel motion (MD, -6.62 hours, 95% CI -8.73 to -4.50 hours, P < 0.00001), shorter length of hospital (SMD, -0.40, 95% CI -0.60 to -0.21, P < 0.0001) than the B/S group. In terms of the subgroup analysis: IA associated with enhanced recovery after surgery (ERAS) group had shorter time to the first flauts (MD, -6.41 hours, 95% CI -9.34 to -3.49 hours, P < 0.0001), shorter time to the first defacation (MD, -6.02 hours, 95% CI -9.28 to -2.77 hours, P = 0.0003) than ERAS group. Conclusion: IA after CRC surgery, acupuncture or electricacupuncture with a fixed number of times and duration at therapeutic acupoints, can promote the recovery of POI. IA combined with ERAS is better than simple ERAS in improving POI.